Ultrahigh tunability of resistive switching in strongly correlated functional oxide. (February 2023) - Pattanayak, Milinda; Hoque, Md Nadim Ferdous; Ho, Yu-Che; Li, Wenyue; Fan, Zhaoyang; Bernussi, Ayrton A.
Highlights: Strongly correlated material. Vanadium dioxide (VO2 ). W-doping. Wx V1-x O2 device. Electrically driven insulator-to-metal transition. Resistive switching. Memristor. Threshold-voltage. Negative differential resistance (NDR). Electro-thermal switching. Neuromorphic voltage oscillation. Resistive memory. Electro-chemical impedance spectroscopy. Finite-element model simulation. Abstract: Vanadium dioxide (VO2 ) is a strongly correlated material that undergoes reversible resistive switching. However, the underlying mechanism of such resistive switching is still under debate. In this work we report an ultrahigh decrease in the VO2 switching threshold-voltage by more than 35 V and a giant 680% change by modifying the material stoichiometry through tungsten (W) doping. This remarkable effect of chemical doping on the resistive switching characteristics of VO2 illuminates on the fundamental mechanism of the insulator-to-metal transition, which reveals that such abrupt resistive switching is attributed to the electro-thermal actuation process. Furthermore, we report ultralow voltage spontaneous electrical oscillation in W-doped VO2 for the first time. Advances achieved here through the design of a new class of transition metal oxide based strongly correlated materials are of paramount importance for emerging electronics.